Oncoplastic Breast Surgery: Is it reliable in the treatment of multifocal breast cancer? A preliminary report of a prospective randomized controlled trial - Awad, Ahmed; Elsayed, Mostafa; Elsayed, Ahmed; Elfayoumi, Tarek; Alhussini, Mahmoud (Journal of Surgery and Medicine, 2021)
Background/Aim: Multifocal breast cancers (MFBCs) still have undiscoverable clinical significance. Being the standard surgical management for early breast cancer, implementation of breast-conservation therapy (BCT) as a surgical procedure for multifocal breast cancers is still questionable and needs a solid basis of clinical evidence via prospective randomized control trials. Methods: A prospective study was conducted on female patients with operable multifocal breast cancer excluding those diagnosed with inflammatory breast cancer and those to receive neoadjuvant therapy. Surgical management was selected randomly and comprised either modified radical mastectomy (MRM) or different techniques of oncoplastic breast surgery (OPS) with a sealed envelope system based on clinical evaluation and recent guidelines for management at the Surgical Oncology Unit, Alexandria University from May 2017-May 2018. The patients were followed up until February 2021 with a median follow-up of 39 months postoperatively to assess recurrence. Analysis of different clinicopathological factors was performed to evaluate the reliability of OPS in the surgical management of MFBCs. Results: A total of 132 patients were initially assessed for the eligibility criteria. Finally, 58 patients in the OPS group and 56 patients in the MRM group were followed up until the end of the study period. After a median follow-up of 39 months post-operatively for both groups, three patients belonging to the oncoplastic group suffered from local recurrence (5.2%). Two patients who had MRM had distant recurrence (3.6%). Although recurrence behavior was different between both groups, this was not statistically significant. Conclusion: OPS is an oncologically safe surgical option for selected cases of multifocal breast cancer.